Etnografias de infâncias calungas: um estudo sobre o cotidiano de crianças de um bairro periférico em São Vicente/SP - Rodrigues, Breno Ayres Chaves [UNIFESP] (2019)
Understanding childhood as a social construction in a time-space and children as subjects of rights that actively participate in this social construction, that is, they produce cultures. In this way we followed up the daily life of 4 children "calunga" (term with African root naming who is born in São Vicente coast of São Paulo) living in a outskirts of the city of São Vicente-SP and attending the "Camará" (a non-governmental organization). Our objective was to increase knowledge about their lives so that this study can subsidize public social policies, in relation to the construction of future actions and projects in line with the reality, language and wishes of this public. For this, a qualitative study was carried out with theoretical and methodological basis on ethnography. The children followed up two girls and two boys, aged between 9 and 12 years. The children acted as coauthors of the present research, that is, they expressed the meanings of their lives and the researcher was the mediator of the organization of these expressions. These same children allowed the access and the sociability in their houses, the circulation in the neighborhood in playful adventures, being in institutional spaces of the NGO, in more serious conversations about dating, violence, culture and others subjects. All these experiences were recorded in field diaries and were organized into categories of analysis, namely: importance of the street to their lives; playful ways of children occupying the neighborhood and the city; its relations with the traffic and the police; sexuality and gender differences; the relationship of children with the NGO involved; and, finally, art, culture and funk dances. The main results were in relation to the inventive and playful ways of moving around the neighborhood they called "missions". In these adventures, they claimed a less "adult-centric" city, transgressing and inventing their own rules of use or practice of spaces. From their collective organization and imagination, which was not neutral to stereotypes and capitalistic signs, they produced new contours and functionalities to the spaces, opening the possibility of resistance to situations that is invisible to the State, such as the lack of spaces for children. The technical product of this research was a children's book that tells a "mission" of 4 black children in a peripheral neighborhood, being accessible material for children, adults, educators and other interested parties.